2013
DOI: 10.1002/dvdy.24092
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sdf‐1α signaling in Xenopus laevis somite morphogenesis

Abstract: Background Stromal derived factor-1α (sdf-1α), a chemoattractant chemokine, plays a major role in tumor growth, angiogenesis, metastasis and in embryogenesis. The sdf-1α signaling pathway has also been shown to be important for somite rotation in zebrafish (Hollway, et al 2007). Given the known similarities and differences between zebrafish and Xenopus laevis somitogenesis, we sought to determine whether the role of sdf-1α is conserved in Xenopus laevis. Results Using a morpholino approach, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…However, recent studies have shown that chemokine molecules play a role in early morphogenesis before the immune system is established. The chemokine ligand xSDF‐1α and its receptor xCXCR4 contribute to the directional migration of mesendodermal cells towards the blastocoel roof during Xenopus gastrulation (Fukui, Goto, Kitamoto, Homma, & Asashima, ), and both knockdown of xSDF‐1α and xCXCR4 affect somite morphogenesis (Leal et al., ). The expression of XCXCLC in the midline region during gastrulation and neurulation promotes lateral–medial directional tissue convergence (Goto & Asashima, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that chemokine molecules play a role in early morphogenesis before the immune system is established. The chemokine ligand xSDF‐1α and its receptor xCXCR4 contribute to the directional migration of mesendodermal cells towards the blastocoel roof during Xenopus gastrulation (Fukui, Goto, Kitamoto, Homma, & Asashima, ), and both knockdown of xSDF‐1α and xCXCR4 affect somite morphogenesis (Leal et al., ). The expression of XCXCLC in the midline region during gastrulation and neurulation promotes lateral–medial directional tissue convergence (Goto & Asashima, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lampreys lack a myoseptum and adaxial cells (Hammond et al, 2009) despite possessing chevron-shaped somites (Rost et al, 2014). Differences in Xenopus and zebrafish have already been recognized with regard to somite rotation, intersomitic boundary formation and other early morphogenic movements in somitogenesis (Afonin et al, 2006;Henry et al, 2005;Leal et al, 2014). This could contribute to the difficulty in making direct comparisons between zebrafish and Xenopus with regard to myosepta, adaxial cells and chevron morphology.…”
Section: Rarβ2 Loss Of Function Reduces Somite Number and Increases Smentioning
confidence: 99%
“…This signaling pathway was also shown to play a role in regulating somite cell rotation in X. laevis . However, the morphogenetic processes underlying somite rotation are quite distinct between X. laevis and zebrafish [14]. …”
Section: Cell Movements Underlying Somite Formationmentioning
confidence: 99%